VSAT- An Efficient, Cost Effective Solution for Connectivity for the Educational Institute: A Case Study - Batish, Sanjay (My University, 2007)
Information technology is an amalgam of some wonderful inventions of the 20th century in electronics and communication. During a very short span of time it has acquired an important place in almost all aspects of human life and particularly in the field of education. The steps taken facilitates in providing effective education in almost all disciplines and particularly for the technical education, to use newer technologies so as to ensure better technical education to all. One such solution is the use of Internet. But as the Internet traffic continues to grow at exponential rates worldwide, Internet services providers (ISP's) everywhere are faced with the challenge of keeping up with demand for network bandwidth and developing creative solutions for squeezing more use out of existing bandwidth. Especially in the developing countries like India where bandwidth requirements are more stringent, such solutions become all the more relevant. Satellite-based Internet connections are one of those solutions. VSAT is one such satellite-based service. VSAT is not new. [1]. In remote and rural areas, where there is little or no terrestrial communications infrastructure, can VSAT platforms prove their value? Making a phone call, surfing the Internet or receiving a fax are everyday functions of life token for granted -- by only 50 per cent of the world's population. For the other half, access to communication systems is far more elusive. The cost and infrastructure build-out needed to link a remote field office of 20 people or a rural community with 100 inhabitants through terrestrial solutions is often too high for operators or governments to undertake. It is in these situations that VSAT platforms -- communication services delivered via satellite-based very small aperture terminals [VSATs] -- have the potential to take center stage. In this thesis we have consider the case study of the complete 10 working of VSAT is given and the performance evaluation of VSAT with leased lines is presented. The usage of VSAT in educational and rural is discussed. It is shown that VSAT provides a cost effective solution for broadband connectivity.
Keywords: Satellite Transponder; Cost Effective Solution